Analytical Treatment for Solving a Class of Non Linear Fractional Differential Equations - Das, Deepanjan (International Journal of Computer Sciences and Engineering, 2019)
In the present paper, generalized differential transform method is used for obtaining the approximate analytic solutions of non-linear partial differential equations of fractional order. The fractional derivatives are described in the Caputo sense.